2015
DOI: 10.1590/1981-6723.5315
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem e propriedades termodinâmicas na secagem de morangos

Abstract: A secagem de produtos agrícolas é largamente utilizada no mundo para diminuir o teor de água do produto, dificultando o crescimento microbiano e a ocorrência de reações químicas e bioquímicas e possibilitando a armazenagem segura por períodos longos, além de reduzir o volume e a massa a ser transportada. O objetivo do presente trabalho foi avaliar e modelar a etapa de secagem de morangos (Fragaria L.), bem como obter parâmetros termodinâmicos em três diferentes temperaturas (40 °C, 50 °C e 60 °C). Foram utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
0
13
0
13
Order By: Relevance
“…The enthalpy changes provide a measure of the energy variation that occurs in the interaction of the water molecules with the constituents of the product during the sorption processes. Entropy is associated with the binding or repulsion of the water molecules of food components in the system and is associated with the spatial arrangement of the water product relationship (Oliveira et al, 2015). Therefore, entropy characterizes the degree of order or disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The enthalpy changes provide a measure of the energy variation that occurs in the interaction of the water molecules with the constituents of the product during the sorption processes. Entropy is associated with the binding or repulsion of the water molecules of food components in the system and is associated with the spatial arrangement of the water product relationship (Oliveira et al, 2015). Therefore, entropy characterizes the degree of order or disorder.…”
Section: Introductionmentioning
confidence: 99%
“…According to Oliveira et al (2015), drying is one of the most well-known and used technologies in the world for ensuring the quality and stability of fresh products during shelf-life. Reduction in the moisture content of material by drying reduces biological activity and chemical or physical changes during the post-harvest procedures and until final consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The positive value is characteristic of adding energy during the drying process, relating the drying of garlic to an endergonic reaction . OLIVEIRA et al (2015), CORRÊA et al (2010) andMARTINS et al (2015) showed similar values for strawberry, coffee cherry and timbó leaf drying studies, respectively. According to OLIVEIRA et al (2015), a non-spontaneous reaction is related to the enthalpy and entropy values, described above, as these reactions occur only when changes in enthalpy are positive and changes in entropy are negative; the variations of these parameters have a positive effect, but the variations are larger for the enthalpy than for the entropy; the changes in the parameters themselves are negative, and the enthalpy change is smaller than the entropy.…”
Section: Thermodynamic Parametersmentioning
confidence: 55%
“…Associating this parameter to the other coefficients observed, it can be stated that for all the temperatures examined, the Midilli model will satisfactorily reflect drying performance, as shown in Table 3. The Midilli model, in general, is the second best fit to agricultural products described by SILVA et al (2015) in drying jenipapo leaves and MELO et al (2015) in drying peppers. However, RADÜNZ et al (2011) discuss that the adjustment of the mathematical model depends upon the plant species, necessitating individual studies at various temperatures and for confirmation.…”
Section: Discussionmentioning
confidence: 99%